Kaitan Sistem Pemiliham Umum dan Korupsi Legislatif Tapanuli Tengah Periode 2015-2020 - Winna Margaretha Hasibuan; Heri Kusmanto; Warjio Warjio (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
Corruption has become one of the most extraordinary phenomena that occur in various democratic countries, including in Indonesia, so that it makes Indonesia ranked 96th in the world as one of the most corrupt countries, and the most dominated by legislative institutions whose members are elected through electoral system. The purpose of this study is to analyze the relationship and corruption factors of the Central Tapanuli legislature by using qualitative research methods with a type of descriptive analysis research and using electoral system theory, legislative corruption and types of political corruption. The results in this study that general election focused on people (people centered) makes political costs very expensive, also makes the attitude of patron-client between the regional head and members of the legislature, and raises a practical political attitude in society and the politicians of Central Tapanuli